UMPSA recognised as 609th Best University in the World in QS WUR, listed among Top 200 THE Impact Rankings - Mimi Rabita, Abd Wahit (UMPSA, 2025)
PEKAN, 19 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has risen to the 609th position globally in the QS World University Rankings (QS WUR) 2026, recently announced.